2018
DOI: 10.1021/acsami.8b09604
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Atomistic Tomography of W-Based Alloyed Two-Dimensional Transition Metal Dichalcogenides

Abstract: Increased interest in two-dimensional (2D) materials and heterostructures for use as components of electrical devices has led to the use of an atomically mixed phase between semiconducting and metallic transition metal dichalcogenides that exhibited enhanced interfacial characteristics. To understand the lattice structure and properties of 2D materials on the atomic scale, diverse characterization methods such as Raman spectroscopy, high-resolution transmission electron microscopy (HR-TEM), and X-ray photoemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Furthermore, these TTMCs have been predicted to be relatively stable owing to their low mixing free energy . Due to outstanding characteristics, TTMCs are regarded as extremely promising candidates for applications in ultrafast photonics and electronics . Theoretical calculations have shown that doping TMCs with group VII elements favors substitutional doping, rather than occupying interstitial and defect sites .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these TTMCs have been predicted to be relatively stable owing to their low mixing free energy . Due to outstanding characteristics, TTMCs are regarded as extremely promising candidates for applications in ultrafast photonics and electronics . Theoretical calculations have shown that doping TMCs with group VII elements favors substitutional doping, rather than occupying interstitial and defect sites .…”
Section: Introductionmentioning
confidence: 99%
“…32 Due to outstanding characteristics, TTMCs are regarded as extremely promising candidates for applications in ultrafast photonics and electronics. 33 Theoretical calculations have shown that doping TMCs with group VII elements favors substitutional doping, rather than occupying interstitial and defect sites. 34 Furthermore, through the introduction of the Re element, 2D TTMCs reveal composition-tunable structural phase transitions and enhanced stability over time, which offer opportunities to study novel phenomena and expand the scope of their application.…”
Section: Introductionmentioning
confidence: 99%
“…As a control group, exfoliated NbSe 2 flakes were prepared under ambient conditions by mechanically exfoliating bulk source materials onto SiO 2 /Si substrates, as previously reported. 30,34,50,51) The exfoliated NbSe 2 flakes were identified using optical microscopy [Fig. 1(a)].…”
mentioning
confidence: 99%
“…Raman spectroscopy was conducted to characterize the atomic vibrational modes of the two differently prepared NbSe 2 samples. 30,34,51) Figure 1 presents the optical micrographs and Raman spectra for a selection of exfoliated NbSe 2 flakes and CVD-grown NbSe 2 . For the exfoliated flake in Fig.…”
mentioning
confidence: 99%